Indigenous Bacteria in Hemolymph and Tissues of Marine Bivalves at Low Temperatures - Olafsen, Jan A. (1993)
Hemolymph and soft tissues of Pacific oysters (Crassostrea gigas) kept in sand-filtered seawater at temperatures between 1 and 8°C were normally found to contain bacteria, with viable counts (CFU) in hemolymph in the range 1.4 × 10(2) to 5.6 × 10(2) bacteria per ml. Pseudomonas, Alteromonas, Vibrio, and Aeromonas organisms dominated, with a smaller variety of morphologically different unidentified strains. Hemolymph and soft tissues of horse mussels (Modiolus modiolus), locally collected from a 6- to 10-m depth in the sea at temperatures between 4 and 6°C, also contained bacteria. The CFU in horse mussel hemolymph was of the same magnitude as that in oysters (mean, 2.6 × 10(4)), and the bacterial flora was dominated by Pseudomonas (61.3%), Vibrio (27.0%), and Aeromonas (11.7%) organisms. In soft tissues of horse mussels, a mean CFU of 2.9 × 10(4) bacteria per g was found, with Vibrio (38.5%), Pseudomonas (33.0%), and Aeromonas (28.5%) constituting the major genera. After the challenge of oysters in seawater at 4°C to the psychrotrophic fish pathogen Vibrio salmonicida (strains NCIMB 2245 from Scotland and TEO 84001 from Norway) and a commensal Aeromonas sp. isolated from oysters, the viable count in hemolymph increased 1,000-fold to about 10(5) bacteria per ml. In soft tissues, about a 1,000-fold increase in CFU to 6 × 10(7) was observed. V. salmonicida NCIMB 2245 invaded hemolymph and soft tissues after 14 days and dominated these compartments after 41 days, whereas strain TEO 84001 did not invade soft tissues to the same extent. Challenge with V. salmonicida NCIMB 2245 resulted in 100% mortality, whereas about 50% of the oysters survived challenge with the Norwegian strain, TEO 84001. The commensal Aeromonas sp. invaded hemolymph and soft tissues and caused 100% mortality. Oyster hemolymph contained agglutinins for Vibrio anguillarum but not for V. salmonicida, whereas we did not find agglutinins for either of these bacteria in horse mussels. Agglutinins for horse and human erythrocytes were found in hemolymph from both animals. We found no differences in agglutinin titers in oysters from different Norwegian locations, and long-term challenge with bacteria in seawater did not result in changes of agglutinin activity. These studies demonstrate that bacteria exist in hemolymph and soft tissues of marine bivalves at temperatures below 8°C. Increased bacterial numbers in seawater at 4°C result in augmented invasion of bacteria in hemolymph and soft tissues. V. salmonicida, a bacterium pathogenic for fish at low temperatures, invades bivalve hemolymph and soft tissues, and thus bivalves may serve as a reservoir for pathogens of fish at low seawater temperatures.